2012
DOI: 10.1063/1.3692086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radiation damage using nonlinear ultrasound

Abstract: Nonlinear ultrasound was used to monitor radiation damage in two reactor pressure vessel (RPV) steels. The microstructural changes associated with radiation damage include changes in dislocation density and the formation of precipitates, and nonlinear ultrasonic waves are known to be sensitive to such changes. Six samples each of two different RPV steels were previously irradiated in the Rheinsberg power reactor to two fluence levels, up to 10 20 n/cm 2 (E > 1 MeV). Longitudinal waves were used to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…Recent studies have also examined ultrasonic absorption for sensitivity to irradiation damage; again, the results are encouraging though based on a limited sample set. Recent studies have also examined the capability of nonlinear ultrasonic measurements to assess irradiation damage (Matlack et al 2012b). While promising, the results are preliminary and require further validation.…”
Section: Acoustic Sensor Materials and Irradiation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have also examined ultrasonic absorption for sensitivity to irradiation damage; again, the results are encouraging though based on a limited sample set. Recent studies have also examined the capability of nonlinear ultrasonic measurements to assess irradiation damage (Matlack et al 2012b). While promising, the results are preliminary and require further validation.…”
Section: Acoustic Sensor Materials and Irradiation Studiesmentioning
confidence: 99%
“…In recent years, nonlinear ultrasonics (NLU) has seen increased interest as a means of characterizing the internal damage state of the material early in the fatigue process (Cantrell and Yost 2001;Matlack et al 2012b). Conventional ultrasonic methods, currently in use in ISI, apply high-frequency (in excess of 500 kHz, typically around 2.25 MHz) acoustic energy and measure the resulting response due to scattering and reflection of the energy at interfaces.…”
Section: Acoustic Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Note that while this measurement setup uses longitudinal waves in a pitch-catch manner, the NLU phenomenon can be measured using other ultrasonic waves including Rayleigh surface waves, Lamb waves, and potentially longitudinal waves in a pulse-receive or double-echo type setup to eliminate the need for a mounted transducer on two opposing faces of the material. Previous work has shown that nonlinear ultrasonic NDE methods are sensitive to radiation damage in RPV steel [63]. The nonlinear ultrasonic parameter was measured on Charpy impact samples of a reference RPV steel material, ASTM A533B Cl.1, at increasing levels of neutron fluence up to 10 20 n/cm 2 (E > 1 MeV).…”
Section: Nonlinear Ultrasonicmentioning
confidence: 99%
“…Numerous researchers have demonstrated the sensitivity of nonlinear ultrasonic techniques to microstructural changes induced by thermal, fatigue, and radiation damage in various alloys [1][2][3][4][5]. A number of theoretical and experimental studies have been conducted to determine the size of the plastic zone in various metallic materials.…”
Section: Introductionmentioning
confidence: 99%